2021
DOI: 10.1002/cpt.2212
|View full text |Cite
|
Sign up to set email alerts
|

Assuring Access to Safe Medicines in Pregnancy and Breastfeeding

Abstract: Scientists and regulators in Europe and the United States continue to seek methods and strategies to improve knowledge on rational use of medicines for pregnant and breastfeeding populations, an important subset of women's health. Regulatory agencies have made strides toward improvement, but much more is needed. Recognizing the importance of international collaboration, we have begun to consider how to address these important public health issues more globally. The health of the child begins with the health of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…One example is pregnant and breastfeeding people and their children ( Figure ). In a joint review from representatives from the UK, EU, and US regulatory agencies, 15 solutions are proposed to improve knowledge on drug safety during pregnancy and breastfeeding, which should reduce current barriers for access to effective medicines in this special population 11,16,17 . For example, opioid use in breastfeeding mothers has increased significantly over the past couple of decades and remains a controversial topic that continues to attract a lot of attention in the scientific literature and media 18 .…”
Section: Figurementioning
confidence: 99%
“…One example is pregnant and breastfeeding people and their children ( Figure ). In a joint review from representatives from the UK, EU, and US regulatory agencies, 15 solutions are proposed to improve knowledge on drug safety during pregnancy and breastfeeding, which should reduce current barriers for access to effective medicines in this special population 11,16,17 . For example, opioid use in breastfeeding mothers has increased significantly over the past couple of decades and remains a controversial topic that continues to attract a lot of attention in the scientific literature and media 18 .…”
Section: Figurementioning
confidence: 99%
“…In this issue of Clinical Pharmacology and Therapeutics, representatives from the major drug regulatory bodies from The United States (the US Food and Drug Administration), Europe (European Medicines Agency), and the United Kingdom (Medicines and Healthcare products Regulatory Agency) propose solutions to reduce the barriers impeding knowledge gain regarding drug safety during pregnancy and breastfeeding. 4 They step through the different stages of drug development, from preclinical testing, clinical trials to postmarketing surveillance.…”
mentioning
confidence: 99%
“…They note "we must move beyond decades of thinking driven by old biases and fear and use sound ethics and safety provisions to make changes encouraging inclusivity." 4 Whereas fear of litigation is often cited as a perceived barrier, an analysis of 10 years of maternity claims from the UK National Health System (NHS) Litigation Authority did not report participation in research trials as a cause of litigation. 6 Analyses of participation of pregnant women in clinical trials of coronavirus disease 2019 (COVID-19) treatments have shown that the tendency to exclude pregnant women from trials has continued.…”
mentioning
confidence: 99%
See 2 more Smart Citations